Tick-Tock Chimes the Kidney Clock - from Biology of Renal Ageing to Clinical Applications - Joshua Rowland; Artur Akbarov; Akhlaq Maan; James Eales; John Dormer; Maciej Tomaszewski (Karger Publishers, 2018)
Ageing of the kidney is a multi-dimensional process that occurs simultaneously at the molecular, cellular, histological, anatomical and physiological level. Nephron number and renal cortical volume decline, renal tubules become atrophic and glomeruli become sclerotic with age. These structural changes are accompanied by a decline in glomerular filtration rate, decreased sodium reabsorption and potassium excretion, reduced urinary concentrating capacity and alterations in the endocrine activity of the kidney. However, the pace of progression of these changes is not identical in everyone - individuals of the same age and seemingly similar clinical profile often exhibit stark differences in the age-related decline in renal health. Thus, chronological age poorly reflects the time-dependent changes that occur in the kidney. An ideal measure of renal vitality is biological kidney age - a measure of the age-related changes in physiological function. Replacing chronological age with biological age could provide numerous clinical benefits including improved prognostic accuracy in renal transplantation, better stratification of risk and identification of those who are on a fast trajectory to an age-related drop in kidney health.